A Pilot Study Assessing the Impact of a High Protein Supplementation Diet on Fat Mass in Obese Adolescents with and without Type 2 Diabetes - Meghana, Gudala; Alexander, Knee; Rushika, Conroy (Journal of Obesity Management, 2016)
Background: Obese adults with Type 2 Diabetes (T2D) have shown differences in body composition and response to varying diets when compared to obese adults without T2D. This difference in body composition affects management options for obesity. Such studies have not been done on adolescents thus far. Objectives: To estimate differences in fat mass at baseline as well as following a two-week high protein liquid diet in obese adolescents with and without T2D. Methods: Thiswas a pilot study using a non-randomized, unblinded pre/post intervention design without a control group. We planned to recruit 40 subjects (20 per group, with and without T2D) from ages 10 – 19 years, with Body mass index (BMI) ≥ 95 percentile. Body fat mass was measured via the Bod Pod® at baseline and after two weeks of following the diet with Ensure High Protein shakes. Change in fat mass is presented as mean differences and 95% confidence intervals. Results: We recruited 28 subjects, 19 completed the study and 12 were compliant with the diet. The mean difference in fat mass percent from baseline in subjects who completed the study (n=19) and without T2D was 1.4 (95% confidence interval (CI): -2.1 to -0.8) and in subjects with T2D was 1.2 (95% CI: -3.6 to 1.24). Conclusion: We did not find any meaningful difference in fat mass at baseline or after following a two-week high protein diet between the groups. High dropout rate and noncompliance with the diet were major limitations.
Keywords: Type 2 Diabetes; obesity; liquid diet; fat mass; body composition